2020
DOI: 10.1590/2177-9465-ean-2019-0158
|View full text |Cite
|
Sign up to set email alerts
|

Training in service: perception of health workers in assistance in federal prison units

Abstract: Objectives: To characterize the in-service training process of health workers from federal prison units. Method: This is a qualitative descriptive-exploratory study. The information was collected through semi-structured interviews with professionals of the referred services, from June to October 2018. Results: Data analysis revealed that health professionals were unaware of the work performed within these establishments and that the concern of these institutions by the improvement of these workers is recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…Barbosa et al 19 and Brito et al 28 differ with Sánchez-Roig et al 26 in stating that professionals showed adequate skills in caring for inmates and adapting to the prison environment, the reason being that the nursing staff considered the inmates to be like any other patient, with their own health problems, and were not felt to be a unique population.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Barbosa et al 19 and Brito et al 28 differ with Sánchez-Roig et al 26 in stating that professionals showed adequate skills in caring for inmates and adapting to the prison environment, the reason being that the nursing staff considered the inmates to be like any other patient, with their own health problems, and were not felt to be a unique population.…”
Section: Discussionmentioning
confidence: 97%
“…De igual manera, Barbosa et al 19 y Brito et al 28 también manifiestan que es necesario reforzar las habilidades y competencias de las enfermeras con respecto al cuidado de los presos mediante una formación continua que se adecúe al entorno penitenciario, al igual que se haría en cualquier otro ámbito de la salud. A la misma conclusión llegan Choudhry et al 29 , puesto que los autores consideran necesario conocer la identidad profesional de la enfermería penitenciaria para comprender cuáles son sus competencias en dicha institución y, así, poder aplicar mejoras en su formación, para conseguir que sea continua y específica, con el fin de que se adecúe a los requerimientos dentro del entorno penitenciario.…”
Section: Discussionunclassified
See 3 more Smart Citations